Model of the interdisciplinary dynamics of the teaching-learning process of Differential and Integral Calculus in the Civil Engineering career - Iglesias Domecq, M. Sc. Nilda; Alonso Berenguer, Dra. C. Isabel (Transformación, 2024)
The current information society demands that civil engineers have an adequate command of the contents of Differential and Integral Calculus as a basis for their successful professional performance. However, there are many national and international reports of learning difficulties of these contents during the undergraduate training period. The objective of this article is to explain the interdisciplinary dynamic that underlies the teaching-learning process of Differential and Integral Calculus by Civil Engineering students. The research methods used were the content analysis of relevant theoretical sources and holistic-configurational modeling. The main result reveals the interdisciplinary logic established between the systematization and engineering functionality of the content of Differential and Integral Calculus and its projective-structural generalization, which constitutes an essential necessary condition for the development of competence for the application of the referred content to the resolution of projective-structural problems.
Keywords: mathematics instructions; applied mathematics; learning; interdisciplinary approach; didactics